La garde-robe des Montréalistes - Back, Francis (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)
Keywords: Vêtements

A Little On the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Université Concordia, 2000)
Keywords: Eaton; Magasins; Montreal Gazette; Publicité

L'underground musical des années 1970 et l'émergence de la "musique actuelle" - Lefebvre, Marie-Thérèse (La contre-culture au Québec, 2016)
Keywords: Musicien; Musique

À la mode du pays - Back, Francis (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)
Keywords: Vêtements

Disunion City: The Fashion of Urban Youth in Montreal, Quebec - Woodhouse, Chelsea (Université de Montréal, 2013)
Keywords: Vêtements

La Montagne vous appelle - Mathieu, Jocelyne (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Femmes; Mont Royal; Patin; Raquetteurs; Ski; Vêtements

L'avènement du patrimoine et la construction de l'image touristique de Montréal - Oualid El Alaoui, Hind (Université du Québec à Montréal, 2015)
Keywords: Patrimoine; Tourisme

L'appropriation de la culture punk: étude ethnographique du punk montréalais en 2015 - Lamarque, Julia (Université du Québec à Montréal, 2016)
Keywords: Musique

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

Defrocking Dad: Masculinity and Dress in Montreal, 1700-1867 - Noel, Jan (Fashion. A Canadian Perspective, 2004)
Keywords: Papineau, Louis-Joseph; Ramezay, Claude de; Redpath, John; Vêtements

Montreal's Fashion Mile: St Catherine Street, 1890-1930 - Sifton, Elizabeth (Fashion. A Canadian Perspective, 2004)
Keywords: Rues; Sainte-Catherine (rue); Vêtements

Mainstreaming the Perception and Practice of Ethical Fashion in Montreal - Craven, Ryan John (Université Concordia, 2009)
Keywords: Vêtements

Fashion and Refuge: The Jane Harris Salon, Montreal, 1941-1961 - Ferrabee Sharman, Lydia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Le costume civil masculin à Montréal au dix-septième siècle - Massicotte, E.-Z. (Mémoires et comptes rendus de la Société royale du Canada, 1939)
Keywords: Costume

Les dessus et les dessous de la mode à Montréal - Back, Francis (Cap-aux-Diamants, 2017)
Keywords: Vêtements

Politicking for Postwar Modernism: The Architectural Research Group of Ottawa and Montreal - Valen, Dustin (Urban History Review / Revue d'histoire urbaine, 2017)

Design and Innovation in Montreal through the 1960s and the 1970s - Sharman, Lydia Ferrabee (Material History Review / Revue d’histoire de la culture matérielle, 2005)
Keywords: Expositions; Place Ville-Marie; Transport en commun

De Montmartre à Broadway: le cabaret Au matou botté de Montréal (1929-1932) - Bellemare, Luc (Mens, 2015)
Keywords: Cabarets; Cafés

Enduring Roots: Gibb and Co. and the Nineteenth-Century Tailoring Trade in Montreal - Cariou, Gail (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Le mouvement Slow Food à Montréal: reflet d'une nouvelle conscience alimentaire cosmopolite - Bélanger, Esther (Université Concordia, 2004)
Keywords: Alimentation

Retailing Fashion in Montreal: A Study of Stores , Merchants and Assortments, 1845-1915 - Sifton, Elizabeth (Université Concordia, 1994)
Keywords: Commerce de détail; Marchands; Vêtements

La mode à Montréal au XXe siècle: un héritage culturel à mettre à jour: rapport à la Direction de Montréal du ministère de la Culture et des Communications du Québec - Baril, Gérald (Institut national de la recherche scientifique - Culture et Société, 1999)
Keywords: Vêtements

Conforme? Une histoire sociale du vêtement masculin chez les élites de Montréal, 1837-1918 - Villeneuve, Louis-Étienne (Université du Québec à Trois-Rivières, 2016)
Keywords: Bourgeoisie; Vêtements

La danse pour tout un chacun: pratiques différenciées d’un loisir commercial à Montréal pendant l’entre-deux-guerres - Roquigny, Peggy (Mens, 2015)
Keywords: Danse

The Changing Face of Fashion in Montreal, 1885-1905: New Markets, Improved Taste and the Move to Mass Production - Payton-Tayler, Evlyn (Université Concordia, 1992)
Keywords: Vêtements

"Bonnie Lassies" and a "Coat of Many Colours": Highland-Inspired Clothing at the McCord Museum - Stack, Eileen (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Musée McCord; Musées; Vêtements; Écossais

Dicomode: dictionnaire de la mode au Québec de 1900 à nos jours - Baril, Gérald (Fides, 2004)
Keywords: Confection; Vêtements

L'Osstidcho ou le désordre libérateur - Roy, Bruno (Documents, 2008)
Keywords: Musique

Fabriquer la tradition canadienne-française : le tabac canadien et la construction de l’identité canadienne-française, 1880-1950 - Rudy, Jarrett (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Tabac